2015
DOI: 10.1007/jhep02(2015)151
|View full text |Cite
|
Sign up to set email alerts
|

Conformal correlators of mixed-symmetry tensors

Abstract: We generalize the embedding formalism for conformal field theories to the case of general operators with mixed symmetry. The index-free notation encoding symmetric tensors as polynomials in an auxiliary polarization vector is extended to mixed-symmetry tensors by introducing a new commuting or anticommuting polarization vector for each row or column in the Young diagram that describes the index symmetries of the tensor. We determine the tensor structures that are allowed in n-point conformal correlation functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 57 publications
(154 reference statements)
8
158
0
Order By: Relevance
“…During the final stages of this work, ref. [14] appeared, where tensors with mixed symmetry are studied. Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the final stages of this work, ref. [14] appeared, where tensors with mixed symmetry are studied. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [14] considers CFTs in arbitrary dimensions, but focuses on bosonic, non-conserved, operators only. When a comparison is possible, the number of tensor structures computed in the examples considered in ref.…”
Section: Discussionmentioning
confidence: 99%
“…16 In fact, the technology to bootstrap four-point functions involving external tensorial operators, while conceptually straightforward, has not yet been fully developed. Rapid progress is being made in the area-see [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117].…”
Section: A Structure Of the Four-point Functionmentioning
confidence: 99%
“…However, the class of conformal blocks derived in this way is associated to the exchange of traceless symmetric operators O, whereas tensor correlator bootstrap requires, in addition, the exchange of mixed-symmetric operators A. Later, in [45,46] it was shown that conformal blocks associated to A can be calculated as a (finite) sum of scalar blocks evaluated at zero spin which, in principle, can be done by a computer. However, the numerical evaluation of these blocks is quite resource intensive due to the fact that the number of terms in the sum increases rapidly with the spin of A.…”
Section: Jhep01(2016)139mentioning
confidence: 99%
“…There is a large body of work on irreducible representations of SO(D) (for instance see the nice discussion in [46] and references therein), but we really don't need the full power of this theory for the current work. Consider a tensor with n indices.…”
Section: A Building Blocks and Identitiesmentioning
confidence: 99%